Framing Families: Neo-Liberalism and the Family Class Within Canadian Immigration Policy - Gabriel, Christina (Atlantis, 2017)
This paper examines the implications of changes to the family class category under Canada’s Immigration and Refugee Protection Act and in particular the introduction of Conditional Permanent Residence (CPR) for sponsored spouses. It raises questions about the extent to which gender mainstreaming as an approach within immigration policy making can actually challenge recent developments, which are animated by familiar neo-liberal rationales but also gesture to a discourse that constructs family class immigrants as “suspicious” and “criminal.”